Direct writing of lead zirconate titanate piezoelectric structures by electrohydrodynamic atomisation. - Rocks, Sophie A.; Wang, D.; Sun, D.; Jayasinghe, S. N.; Edirisinghe, M. J.; Dorey, Robert A. (Springer Science Business Media, 2007)
Direct writing, consisting of the directed deposition of individual droplets of ceramic suspension using ink jet printing can be used to produce piezoelectric structures with feature sizes in excess of 100 μm. This work presents an alternative direct writing technique, consisting of directed individual droplets produced by electrohydrodynamic atomisation (EHDA), where feature sizes an order of magnitude smaller can be achieved. This technique opens up the possibility of using direct writing technology to produce integrated MEMS devices. Low toxicity lead zirconate titantate (PZT) sol has been used in conjunction with the EHDA process to produce isolated features and lines with dimensions as small as 20 μm. These features, when fired, form the perovskite PZT crystal structure. Using an X–Y stage to move the sample, it is possible to create a variety of structu
Keywords: 3D structures; Direct printing; PZT; Electrohydrodynamic; EHDA